Massive retroperitoneal haemorrhage after extracorporeal shock wave lithotripsy (ESWL) - Inoue, Hiromasa; Kamphausen, Thomas; Bajanowski, Thomas; Trübner, Kurt (International Journal of Legal Medicine, 2011)
A 76-year-old male suffering from nephrolithiasis developed a shock syndrome 5 days after extracorporal shock wave lithotripsy (ESWL). CT scan of the abdomen showed massive haemorrhage around the right kidney. Although nephrectomy was performed immediately, the haemorrhage could not be controlled. Numerous units of erythrocytes were transfused, but the patient died. The autopsy revealed massive retroperitoneal haemorrhage around the right kidney. The kidney showed a subcapsular haematoma and a rupture of the capsule. The right renal artery was dissected. The inferior vena cava was lacerated. Accordingly, a hemorrhagic shock as the cause of death was determined, which might mainly have resulted from the laceration of the inferior vena cava due to ESWL. ESWL seems to be a relatively non-invasive modality, but one of its severe complications is perirenal hematoma. The injuries of the blood vessels might have been caused by excessive shock waves. Subsequently, anticoagulation therapy had been resumed 3 days after EWSL, which might have triggered the haemorrhage. Physicians should note that a haemorrhage after an ESWL can occur and they should pay attention to the postoperative management in aged individuals especially when they are under anticoagulation therapy. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2025-02-28
Keywords: ESWL; Hemorrhagic shock; Laceration of the inferior vena cava; Nephrectomy; Perirenal haemorrhage